Law enforcement against environmental damage using and environmental law approach. Issue 1 (October 2021) - Jadda, Asram A.T.; Arfin Hamid, M.; Yunus, Muhammad; Irwansyah
Abstract: Damaging the environment is a serious violation for the sustainable life of humanity. This research aims at how the law enforcement against the environmental damage using Al-Qur'an and Environmental Law approach. This research using a normative legal study. The result of this research is showed that Al-Qur'an regulates several human behaviors which can damage or triggering environmental damage, such as: acts of human physically and human behavior that exceed the limit of religious and human norms. Environmental law regulates human behavior to preserve and prohibiting environmental damage.